On-farm research to improve smallholder livestock productivity in the Ethiopian highlands - Gryseels, Guido; Anderson, F.M.; Asamenew, G.; Mesgina, A.; Astatke, A.; Wolde-Mariam, W.A. (1989)
Summarises the results of on-farm research conducted by the Highlands Programme (ILCA) in order to improve smallholder livestock productivity in the Ethiopian Highlands. Outlines the farming system around Debre Berhan. Discusses on farm trials and research activities on the integration of crossbred cows and forages in the farming system, use of single oxen for crop cultivation, use of oxen for pond excavation and improved cultivation techniques for vertisol development.